Unsuspected Cause of Respiratory Distress: Unrecognized Esophageal Foreign Body - Naima Baddouh; Lahcen Arjdal; Abdelaziz Raji; Mounir Bourrous (Case Reports in Pediatrics)
Summary. Foreign bodies in esophagus are avoidable accidents that occur most often in children younger than 3 years. The most common presenting symptoms are dysphagia, drooling, and vomiting. Revelation by respiratory distress is a rare and unusual condition. Objective. We describe and discuss the case of an esophageal foreign body, in which the patient presented with respiratory distress. Case report. A two-year-old child was admitted to the emergency department for acute respiratory distress. He had no history of choking episodes or dysphagia. Nevertheless, he was brought by his parents several times for a persistent cough and wheezing that was treated as asthma for a month. Pulmonary examination had revealed polypnea, suprasternal recession, scattered snoring, and diffuse wheeze. As part of his assessment, a chest X-ray was demanded. It had shown, as unexpected, a nonmetallic foreign body in the upper thoracic esophagus. A clothing button was removed by hypopharyngoscopy under sedation without any incident. Subsequent follow-up had not shown any complications related to this episode. Conclusion. Large esophageal foreign bodies can impinge on the trachea causing upper respiratory tract signs. We alert clinicians on variation in the presentation of foreign body ingestion, and we emphasize the importance of an early diagnosis and management.